2004
DOI: 10.1080/10428190410001712234
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Serum Levels of IL-10 are Associated with Inferior Progression-Free Survival in Patients with Hodgkin's Disease Treated with Radiotherapy

Abstract: Elevated pretreatment serum interleukin-10 (IL-10) is associated with inferior progression-free survival (PFS) in patients with Hodgkin's disease (HD) treated with ABVD or equivalent regimens. Therefore, we explored the association of serum IL-10 with presenting features and PFS in HD patients treated only by radiotherapy (RT) with curative intent. Eligible patients were previously untreated, had biopsy-proven HD, were older than 16 years, HIV-negative, and had unthawed pretreatment serum. Serum IL-10 levels w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
30
0
2

Year Published

2005
2005
2010
2010

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 13 publications
1
30
0
2
Order By: Relevance
“…2,3,5,6 This is in agreement with our observations and can help to explain why patients with the IL10-3575AA genotype have a better overall survival. However, we did not have measurements of IL-10 production and a more detailed statistical analysis was limited by the small number of cases in each lymphoma category.…”
Section: © F E R R a T A S T O R T I F O U N D A T I O Nsupporting
confidence: 81%
See 1 more Smart Citation
“…2,3,5,6 This is in agreement with our observations and can help to explain why patients with the IL10-3575AA genotype have a better overall survival. However, we did not have measurements of IL-10 production and a more detailed statistical analysis was limited by the small number of cases in each lymphoma category.…”
Section: © F E R R a T A S T O R T I F O U N D A T I O Nsupporting
confidence: 81%
“…It has also been described that patients with high IL-10 production have a worse prognosis. 3,5,6 A number of polymorphisms of the IL-10 gene promoter have been described. These include two biallelic polymorphisms at positions -1082 (G to A substitution), and -3575 (T to A substitution).…”
mentioning
confidence: 99%
“…In our opinion, the lack of a significant association between serum levels of BLyS and IL-10, which has been reported as a marker that is strictly related to disease activity (Visco et al, 2004), may be due either to the small number of our series or to an independent role of these two molecules in HL.…”
Section: Discussionmentioning
confidence: 51%
“…Interestingly the same group, Chiu et al (2007) has demonstrated that the signals (Novak et al, 2002(Novak et al, , 2004a. Furthermore, an involvement of BLyS in HL was suggested by the fact that IL-10, a pleiotropic cytokine also involved in HL pathogenesis (Visco et al, 2004), regulates BLyS expression and release by myeloid cells (Nardelli et al, 2001). Among NHL patients, a significant correlation between high pre-treatment sBLyS levels and the presence of B symptoms, elevated LDH and an inferior overall survival has been previously demonstrated only in diffuse large B-cell lymphoma (DLBCL) (Novak et al, 2004b).…”
Section: Discussionmentioning
confidence: 99%
“…Esses autores sugerem que a IL-10 sérica poderia ser considerada um fator prognóstico independente das variáveis clínico-laboratoriais clássicas, consideradas pelo IPI, e que a esta citocina poderia auxiliar na identificação precoce de pacientes que necessitariam de tratamento mais agressivo ao diagnóstico. 5,[9][10][11][12][13][14][15][16][17] Sabe-se que a IL-10 é produzida por linfócitos Th2 e tem função inibitória sobre a produção de INF-γ e IL-2, regulando negativamente a imunidade celular Th1. 6,8 Portanto, de acordo com os nossos resultados e os dados da literatura, a IL-10 sérica elevada, no grupo de pacientes com variáveis que implicam pior prognóstico, poderia estar regulando ne-gativamente uma resposta imune Th1 ou citotóxica, contribuindo assim com a progressão da doença.…”
Section: Discussionunclassified